COVID-19 Impact on Major Stock Markets. Issue 3 (September 2022) - Gupta, Hemendra; Chaudhary, Rashmi; Gupta, Suneel
COVID-19 is one of the unprecedented global crises that hit mankind in the last 100 years. It has engulfed the entire globe in its ambit, and what makes it peculiar is that it is not an economic crisis like the Great Depression or the Financial Crisis in 2007, but this is a natural crisis. The crisis has brought the entire global economy to a standstill due to lockdowns across different geographies, which has retarded the growth of economies. The current study explores how different major stock markets across the world have reacted to this grave pandemic. It is studied by comparing the returns of different phases of the market with the normal phase by applying T -test and Mann–Whitney U -test. Results indicate the short-term impact of this epidemic and much faster recoveries across different markets. The study also explores the spillover effect of different markets over others.